2011
DOI: 10.1097/cad.0b013e328346c7d6
|View full text |Cite
|
Sign up to set email alerts
|

Comparative study of transfersomes, liposomes, and niosomes for topical delivery of 5-fluorouracil to skin cancer cells

Abstract: Topical 5-fluorouracil (5-FU) is used for the treatment of actinic keratosis and nonmelanoma skin cancer. Unfortunately, 5-FU per se shows a poor percutaneous permeation, thus reducing its anticancer effectiveness after topical administration. Therefore, we have constructed transfersomes, liposomes, and niosomes of 5-FU for topical applications in this investigation. Transfersomes were prepared by the solvent evaporation method, whereas liposomes and niosomes were constructed by reverse-phase evaporation metho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
34
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 104 publications
(37 citation statements)
references
References 0 publications
3
34
0
Order By: Relevance
“…Vaccines, 5-fluorouracil, IL-2 and IFN-α [149][150][151] SECosomes or nanosomes Mixture of surfactant, ethanol and cholesterol siRNA [121] SLNs Produced with one single solid lipid and surfactants, with perfect crystalline lattice CoQ-10, glucocorticoids, minoxidil and oxybenzone [152][153][154][155] NLCs Produced with solid and liquid lipids and surfactants, with distorted crystalline lattice Targeted tumor delivery, phospholipase A2 inhibitors, benzocaine, lidocaine and psoriasis treatment [156][157][158][159] Polymeric nanoparticles Consist of micro-and nano-spheres or capsules developed to control the release of the entrapped drug Chlorhexidine, indomethacin, melatonin and poorly soluble drugs [160][161][162][163] ALA: Aminolevulinic acid; NLC: Nanostructured lipid carrier; SECosome: Surfactant-ethanol-cholesterol-osome; SLN: Solid lipid nanoparticle.…”
Section: Nanoemulsion or Microemulsionmentioning
confidence: 99%
“…Vaccines, 5-fluorouracil, IL-2 and IFN-α [149][150][151] SECosomes or nanosomes Mixture of surfactant, ethanol and cholesterol siRNA [121] SLNs Produced with one single solid lipid and surfactants, with perfect crystalline lattice CoQ-10, glucocorticoids, minoxidil and oxybenzone [152][153][154][155] NLCs Produced with solid and liquid lipids and surfactants, with distorted crystalline lattice Targeted tumor delivery, phospholipase A2 inhibitors, benzocaine, lidocaine and psoriasis treatment [156][157][158][159] Polymeric nanoparticles Consist of micro-and nano-spheres or capsules developed to control the release of the entrapped drug Chlorhexidine, indomethacin, melatonin and poorly soluble drugs [160][161][162][163] ALA: Aminolevulinic acid; NLC: Nanostructured lipid carrier; SECosome: Surfactant-ethanol-cholesterol-osome; SLN: Solid lipid nanoparticle.…”
Section: Nanoemulsion or Microemulsionmentioning
confidence: 99%
“…Due to the unfavorable skin permeation profile of 5-fluorouracil in conventional formulations, there has been an increased interest in the use of drug delivery systems to deliver 5-fluorouracil into the deeper layers of the skin. Research has been carried out on the topical delivery of 5-fluorouracil using drug delivery systems such as ethosomes (12) niosomes, liposomes, transfersomes (13), and nanogels (14). In these studies, it showed that the drug delivery systems resulted in an increase in either the flux or retention of API in the skin layers.…”
Section: Introductionmentioning
confidence: 99%
“…The topical application of transfersome-entrapped anticancer drug is described by a few research groups. Skin delivery of 5-fluorouracil (5-FU) [32,33,34], methotrexate, and bleomycin has been evaluated by many researchers. Edge activators are often single chain surfactant that destabilizes lipid bilayers of the vesicles and provides a flexible membrane, eventually making transfersomes highly flexible.…”
Section: Merits/demeritsmentioning
confidence: 99%
“…The in vivo results concluded that vesiculization of 5-FU not only improves the topical delivery, but also enhances the cytotoxic effect of 5-FU [87]. An instance of transfersomal gel containing 5-FU provided efficient results against the treatment for AK and non-melanoma skin carcinoma, which showed up to a twofold increase of transdermal release in contrast to other marketed formulations [88].…”
Section: Applicationsmentioning
confidence: 99%
See 1 more Smart Citation